MANFAAT XANTHONE TERHADAP KESEMBUHAN ULKUS RONGGA MULUT DILIHAT DARI JUMLAH SEL PMN DAN FIBROBLAST - Lanny Sunarjo; Ratnawati Hendari; Hermien Rimbyastuti (ODONTO : Dental Journal, 2015)
Background: ulcer is a pathological condition characterized by the loss of epithelial tissue. The average prevalence of ulcers in the oral cavity ranges between 15-30%. Paste of mangosteen rind which agent called xanthone can accelerate ulcer healing process, however histopathological observation of PMN (Polymorphonuclear) numbers and fibroblasts cells are required.Purpose: to determine the ability of mangosteen rind in treating ulcers caused by infection, mechanical and chemical trauma from the numbers of PMN and fibroblasts cells.Method: experimental studies, pre-posttest control group design, with randomized technique, total sample of 36 Male Wistar rats were divided into 6 groups @ 6 where 3 treatment groups were smeared paste of rind mangosteen and the others without treatment, then from each group were decapitated onday 3rd, 7th and 10th. Result: Ulcer from mechanical and chemical trauma had been healing on 7th day compared with untreated on 9th day. Similarly ulcer infection has been healing on 9th day compared with untreated on 10th day. Anova test(repeated) shows that there is diameter difference significantly between day 1 to 8 (pvalue<0,001). The usage of xanthone decreases amount of PMN cells during inflammation phase and increases amount of fibroblast cells during proliferation phase.Conclusion: xanthone could accelerate healing process as well as shrinkage of ulcus diameter compared with untreated ulcer.